2019
DOI: 10.21106/ijma.287
|View full text |Cite
|
Sign up to set email alerts
|

HIV Non-Occupational Post Exposure Prophylaxis in Nigeria: A Review of Research Evidence and Practice.

Abstract: Background: Although non-occupational Human Immunodeficiency Virus (HIV) post-exposure prophylaxis (nPEP) has been proven to be efficacious in preventing HIV, it remains an underutilized prevention strategy in Nigeria. We aimed to conduct an overview of research studies on nPEP and practice in Nigeria from 2002 to 2018 examining: sociodemographic characteristics of study sample, awareness, knowledge and prior use of nPEP, reasons for HIV nPEP, timeliness in presenting for PEP, antiretrovirals (ARVs) used for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
(119 reference statements)
2
4
0
Order By: Relevance
“…A systematic review in Nigeria also found 23.8% of the patients could not finish treatment induced by SEs. [49] Treatment completion was associated with SEs in our study. All these…”
Section: Medication Uptake and Sessupporting
confidence: 47%
See 1 more Smart Citation
“…A systematic review in Nigeria also found 23.8% of the patients could not finish treatment induced by SEs. [49] Treatment completion was associated with SEs in our study. All these…”
Section: Medication Uptake and Sessupporting
confidence: 47%
“…A systematic review in Nigeria also found 23.8% of the patients could not finish treatment induced by SEs. [ 49 ] Treatment completion was associated with SEs in our study. All these suggest ongoing adherence education, medication guidance, and psychological supports are essential in the course of nPEP for avoiding non-compliance.…”
Section: Discussionmentioning
confidence: 56%
“…According to the findings of the current research and previously conducted studies in different countries, the most common consumers of nPEP are represented by the persons who had risky sexual contact (with partner of unknown or HIVpositive status), MSM group representatives, victims of sexual assault [12,13,21,22]. Nevertheless, nPEP may be considered underutilized strategy in HIV response actions [10,28,29].…”
Section: Awareness Of Npep Among Beneficiaries Of Servicementioning
confidence: 79%
“…This finding was similar to the results of the studies from the United States [ 17 ] and Europe [ 18 , 19 ] where nPEP was mostly sought by young men. In Africa, [ 20 , 21 ] however, participants were predominantly young women, and the most frequent reason for seeking nPEP was sexual assault.…”
Section: Discussionmentioning
confidence: 99%